Interstitial small stories in Sandton, Gauteng, South Africa - Kelleher, William (Stellenbosch Papers in Linguistics Plus, 2022)
Interstices are those residual, left-over, spaces associated with movement across and between urban forms. Interstices in the business district of Sandton, Gauteng, South Africa, represent the insurgence of the lower levels in the vertical push of the high-rise offices, luxury hotels and retail spaces of the district. In interstitial spaces encounters and interactions are often fleeting and contingent. There is a discontinuity of social space. Links between people are spread out over the grid of the city, disassembled and reassembled as people leave their homes, move through different transport nodes to different destinations in the district and there, in turn, continue and discontinue their trajectory. Interstitial stories capture a reticular activity that binds people together through movement and space. In terms of narrative research, interstitial stories, a type of ‘small’ story, offer particularities that concern the intersection of the spatiality and temporality of the real and diagetic worlds, linguistic representational means and social consequentiality. The aim of this article is to explore interstitial stories, as an instantiation of small stories research and as a local storytelling practice, through three extracts that represent three different configurations of space and time: superposed spatialities, temporal and spatial identity, and movement in telling trajectory. In analysing these stories, this article hopes to shed further light on the role that narrative plays in our daily lives and interactions, bringing out local conditions and linguistic repertoires in the global South. Interstices emerge as challenging, cooperative and familiar, and, in contradistinction to what their name could imply, a strong resource for identity construction.